Screening and characterization of integration sites based on CRISPR-Cpf1 in Pichia pastoris - Shupeng Ruan; Yuxin Yang; Xinying Zhang; Guanjuan Luo; Ying Lin; Shuli Liang (Synthetic and Systems Biotechnology)
Pichia pastoris, a methylotrophic yeast, can utilize methanol as a carbon source and energy source to synthesize high-value chemicals, and is an ideal host for biomanufacturing. Constructing the P. pastoris cell factory is somewhat impeded due to the absence of genetic tools for manipulating multi-gene biosynthetic pathways. To broaden its application in the field of metabolic engineering, this study identified and screened 15 novel integration sites in P. pastoris using CRISPR-Cpf1 genome editing technology, with EGFP serving the reporter protein. These integration sites have integration efficiencies of 10–100 % and varying expression strengths, which allow for selection based on the expression levels of genes as needed. Additionally, these integrated sites are applied in the heterologous biosynthesis of P. pastoris, such as the astaxanthin biosynthetic pathway and the carbon dioxide fixation pathway of the Calvin-Benson-Bassham (CBB) cycle. During the three-site integration process, the 8 genes of the CBB cycle were integrated into the genome of P. pastoris. This indicates the potential of these integration sites for integrating large fragments and suggests their successful application in metabolic engineering of P. pastoris. This may lead to improved efficiency of genetic engineering in P. pastoris.